NEUROBLASTOMAS OF MAXILLOFACIAL LOCALIZATION OF A NEWBORN CHILD - P. I. Tkachenko; M. O. Cholovskyi; O. B. Dolenko; S. O. Belokon; Y. V. Popelo (Український стоматологічний альманах, 2019)
Neuroblastoma in newborns is a fairly rare disease and affects 6-8 children per million children. It can be combined with congenital defects, has a tendency to metastasize and to spontaneous maturation in ganglioneuritis, which can simulate various diseases and significantly complicate its diagnosis. This publication provides clinical observations of a newborn baby with a neuroblastoma located in the maxillofacial area. Attention is drawn to the difficulties encountered in establishing a clinical diagnosis, to address questions about this, it is recommended that modern, highly informative methods of examination be more widely involved in examining such children, preferably in the early stages of the disease. Against the background of an unceasing increase in the number of malignant neoplasms of the maxillofacial area among the Ukrainian population, directly among the residents of the Poltava region, this figure is 2.3% of the total number of newly diagnosed malignant formations. Asymptomatic course and "erosion" of clinical manifestations of tumors at their initial stages of development, the untimely treatment of patients with specialized assistance against the background of inadequate awareness among citizens and healthcare professionals in this section of medicine and their lack of oncological anxiety leads to the fact that a significant proportion of patients falls on treatment with abandoned forms. In particular, according to the statistical reporting of the Poltava regional oncologic dispensary at stages III and IV, the malignant process in the tissues 41.6%, of which 54% is cancer of the oral mucosa, from 28%, where the cancer of the tongue is in 10% of cases of lung cancer and 8% diagnosed salivary gland cancer. It is rather unfortunate, but in 55% of the observations, the cause of late treatment is organizational and methodological disturbances: not enough complete examination of patients, to the hospital stage (underestimation of clinical data, X-ray changes, incorrect interpretation of the results of additional methods of examination), insufficient prophylactic work among the general population or a sequence of its planning, poor quality preventive examinations, delayed patients in the grass-roots of medical institutions. In spite of the fact that a significant proportion of organs and tissues of maxillofacial area are available for objective and application of additional methods of examination, about 40% of patients have launched forms of malignant processes due to the faults of doctors [2, 3, 5, 8]. In nursery practice, the situation does not look better, since in Ukraine, 3.5% of cases of malignant tumors are diagnosed annually in Ukraine. Unfortunately, in periodicals there are isolated data on primary and metastatic lesions of maxillofacial area in children, although the recognition and treatment of oncosomatic diseases in them in the early stages of development to date present considerable difficulties due to the large variety of clinical manifestations of tumors, age-specific features, dependence of diagnosis malignant neoplasms from the dynamics of growth, localization, local and general changes [6,7]. Therefore, in our opinion, the number of diagnostic errors in children's practice is greater than in adults. The problem is of general medical significance also because, due to topographic and anatomical features of the structures of the head and neck, any pathology of maxillofacial localization is the subject of participation of doctors in various related specialties. Thus, the given clinical case indicates the possibility of a malignant effect of tissues and organs of a child already during the period of fetal development, which greatly complicates the diagnostic procedure and should alert doctors of all specialties.